Numbers of Light-bellied Brent Geese Branta bernicla hrota staging in Iceland in spring - Gardarsson, Arnthor; Gudmundsson, Gudmundur A (Wildfowl, 1996)
Light-bellied Brent Geese that stage in west Iceland in spring were censused in mid May 1974, 1986, 1990, 1995 and 1996. The results are compared with censuses from the winter range of this population, in Ireland. In 1974 about 7,200 Brent Geese were recorded, in 1986 they totalled at least 15,700, in 1990 13,800, in 1995 15,900 and in 1996 17,400. Numbers each spring were about equally split between the bays Faxafloi and Breidafjrdur, but the distribution in Faxafloi shifted considerably south during the period.